Register analysis of women’s fashion online shop sellers in live shopping sessions - Sijabat, Carissa Margaret; Khansa, Syifa Nadiah; Marsha, Sit Azzahra; Sitompul, Muhammad Riyadhil; Rangkuti, Rahmadsyah (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This study investigates the language registers employed by women’s clothing sellers during TikTok Live sessions, emphasizing the specific words and phrases to promote communication in a fast-paced sales environment. Through qualitative investigation of live-stream interactions, the study finds that nouns (41.86%) are predominantly used to provide detailed product descriptions, followed by verbs, adjectives, abbreviations, and compound words. Nouns convey information about stock availability, sizes, and materials.  The study differentiates between lexical and contextual meanings, with lexical meanings (60.47%) taking precedence, providing precise definitions that improve intelligibility for potential purchasers. Lexical meanings enhance clarity and understanding for potential buyers, while contextual meanings, though less frequent, are vital for maintaining dynamic interaction with the audience. These findings highlight the sellers' strategic use of clear product descriptions and conversational language to boost audience engagement and drive sales. This study suggests that the language strategies used on TikTok Live Sessions are adaptable, effectively balancing product clarity with audience interaction to optimize the sales process.